Determinatino of Elemental Concentrations in Fish and Sediments from Rize-Ardesen Area of the East Black Sea - AKYUZ, TANIL; AKYUZ, SEVIM (Asian Journal of Chemistry, 2010)
Some elemental concentrations (K, Ca, Cr, Mn, Fe, Cu, Ni, Zn, Br, Cd, Rb, Sr, Ba, Cs, Zr, Sb, Pb, ) of 7 fish species (anchovy, red mullet, grey mullet, sea pike, horse mackerel, whiting and sea-bream), which are largely consumed by human, together with two surface sediment samples from Rize- Ardesen area of the Turkish coast of the east Black Sea have been analyzed by EDXRF spectrometry. Pb was only detected in horse mackerel (2.1 mg/kg) among the muscles of fish species. The results indicated that Mn, Fe, Ni, Cu, Zn and Br were more concentrated in the livers of the fish samples than in muscles, whereas Rb, Sr and Zr concentrations were lower in livers than that in muscles. A positive correlation was found between concentrations of Zn, Cu, Ni and Pb in the sediment and in fish species. The analysis results of the fish samples are compared with those of other marine environment.